Dynamic response of metallic lattice sandwich structures to impulsive loading - Cui, Xiaodong; Zhao, Longmao; Wang, Zhihua; Zhao, Han; Fang, Daining (International journal of impact engineering, 2012)
The dynamic response of metallic lattice sandwich plates under impulsive loading is studied by experimental investigation. The sandwich structures composed of two identical face sheets and tetrahedral lattice cores, were designed and fabricated through perforated metal sheet forming and welding technology. The air blast experiment of lattice sandwich structures was performed by use of a four-cable ballistic pendulum system. The deformation/failure mechanisms were investigated through experimental observation and analysis. The impulsive resistance of the tetrahedral lattice sandwich structures is quantified by the maximum permanent transverse deflection of the back face sheet as a function of transmitted impulse. The maximum transverse deflections of tetrahedral lattice sandwich plates are compared with that of hexagonal honeycomb ones with identical parent materials and core relative density. The comparison implies that the tetrahedral lattice sandwich structures possess a better impulsive resistance.